The role of religious ideologies in children's expectations about moral and conventional norm violations - Serbest, Oya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Previous research shows that children differentiate religious groups and expect different behaviors from them starting from 5 years of age. This study aimed to understand how children’s expectations from religious groups change across social norm domains and age. In this online study, 81 6-7-year-olds and 80 9-10-year-olds were recruited and introduced to characters with contrasting religious beliefs based on randomly assigned conditions. Characters were Muslim-believers and disbelievers in one condition and were Muslim-believers and non-Muslim believers in the other condition. Across four trials, children were asked about which characters might have violated a moral or conventional norm. Then, they were asked about whom they would trust and play with, and which character is most like them. Overall, children expected more norm violations from disbelievers than believers. Older children attributed more norm violation to non-Muslims than younger children. Younger children expected more conventional violations from disbelievers, whereas older children expected more moral violations (vs. non-Muslim believers). Compared to younger children, older children expected more moral violations from disbelievers and conventional violations from non-Muslim believers (vs. Muslims). Also, children of all ages trusted Muslim characters more than non-Muslim characters, and this trend strengthened with age. On the other hand, children preferred to play with Muslims over non-Muslims, except younger children who were introduced to Muslim and non-Muslim believer characters. In sum, these results show that children judge religious groups in a nuanced way; yet their expectations from and attitudes toward those groups might change during elementary school years.
Keywords: Children -- Religious life.; Experience (Religion) in children.